(untitled) (Research, Society and Development, 2023)
Introduction: Music acts on specific areas of the brain, stimulating its plasticity, bringing numerous contributions in various situations, such as, for example, reducing anxiety, stress levels, increasing cognitive, intellectual, spatial abilities, among others. The general objective of this study is to understand the benefits provided by music in promoting health due to its neurochemical effects. Methodology: a literature review was carried out that allowed the search for articles published in the last ten years, by Brazilian and foreign researchers, in the Pubmed and Google Scholar databases. Results and discussion: The data obtained allowed us to verify that music therapy, carried out by specialized professionals, helps patients with different health/disease conditions to improve their physical, intellectual, emotional and social conditions due to the musical stimuli received. Considerations: The stimuli from music act on the brain and its plasticity, culminating in positive effects, whether in the treatment of people with anxiety, depression, who need to go through the neuro rehabilitation process, elderly people who are suffering from a lack of memory, among other conditions. It also helps healthcare professionals work with more motivation, providing more humanized care to the patients they serve.